Incidence and mortality of ischemic stroke subtypes in Joinville, Brazil: a population-based study - Marcos C. Lange; Norberto L. Cabral; Carla H. C. Moro; Alexandre L. Longo; Anderson R. Gonçalves; Viviane F. Zétola; Tatjana Rundek (Arquivos de Neuro-Psiquiatria)
Aims To measure the incidence and mortality rates of ischemic stroke (IS) subtypes in Joinville, Brazil. Methods All first-ever IS patients that occurred in Joinville from January 2005 to December 2006 were identified. The IS subtypes were classified by the TOAST criteria, and the patients were followed-up for one year after IS onset. Results The age-adjusted incidence per 100,000 inhabitants was 26 (17-39) for large-artery atherosclerosis (LAA), 17 (11-27) for cardioembolic (CE), 29 (20-41) for small vessel occlusion (SVO), 2 (0.6-7) for stroke of other determined etiology (OTH) and 30 (20-43) for stroke of undetermined etiology (UND). The 1-year mortality rate per 100,000 inhabitants was 5 (2-11) for LAA, 6 (3-13) for CE, 1 (0.1-6) for SVO, 0.2 (0-0.9) for OTH and 9 (4-17) for UND. Conclusion In the population of Joinville, the incidences of IS subtypes were similar to those found in other populations. These findings highlight the importance of better detection and control of atherosclerotic risk factors.